Demand for broad money in Singapore: does wealth matter? - Baharumshah, Ahmad Zubaidi; Soon, Siew-Voon (Springer, 2015)
We present a stable long-run relationship between real money balances and its determinants, including asset prices, to capture wealth effects. The major findings are, first, asset (housing) prices have a noticeable, positive, and a significant effect on the demand for broad money in Singapore. Developments in the housing market alter the structure of money demand and, so, may complicate the conduct of monetary policies. Second, no evidence of a monetary overhang is found, and the augmented wealth model passes a battery of diagnostic tests. Third, the results confirm that the estimated model is invariant to policy changes and, consequently, immune to the so-called Lucas critiques.